Topology optimization and shape design method for large-span tensegrity structures with reciprocal struts. (1st December 2020) - Su, Yan; Zhang, Jingyao; Ohsaki, Makoto; Wu, Yue
Abstract: Tensegrity is a kind of efficient structural system that is composed of continuous cables in tension and discontinuous struts in compression. Although the studies on tensegrity have been carried out by many researchers, there are few methods for assembling large-span tensegrity by multiple units. Inspired by the similarities between reciprocal units and tensegrity units, we present a novel method for designing large-span tensegrity structures with reciprocal struts, which is a kind of new tensegrity structural system that can cover a large area, while the rule of discontinuous struts is followed strictly. The proposed design method includes assembly, topology optimization, and shape design. The prototype; i.e., initial topology, of the tensegrity is generated from reciprocal struts. A topology optimization method using ground structure approach is proposed to remove the redundant cables from the initial topology. A shape design method using fictitious stiffness parameters is proposed to satisfy the architectural shape demand. The form-finding problem, which is to find the self-equilibrium shape in the topology optimization as well as shape design processes, is solved by using the non-rigid-body motion analysis method. Numerical examples demonstrate the effectiveness and applicability of the proposed method.